ANALISIS RASIO LIKUIDITAS DAN RENTABILITAS PADA KINERJA KEUANGAN UMKM ANGKRINGAN GOPEL DI DESA CANGKRINGMALANG - Singgih Nurdiyanto (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2022)
Micro, Small and Medium Enterprises are businesses that started as family industries. MSMEs play a very large role in the progress of the Indonesian economy, although have shown their role as drivers of the national economy, are still experiencing difficulties or obstacles, both internal and external. This study aims to determine the effect of liquidity ratios and profitability ratios on the financial performance of Angkringan Gopel during 2016-2020. This research method is explanatory research using quantitative research. The sample used in this study is the sample used in this study is data from financial reports for 5 years, namely from 2016 to 2020, the source of data used in this study is data secondary. Data analysis using multiple linear regression analysis and hypothesis testing, with SPSS data processing. The results of the study conclude that there is a significant effect of the Liquidity Ratio calculated by the current ratio on the financial performance of Angkringan Gopel during 2016-2020, there is a significant effect of the Profitability Ratio calculated by Gross Profit margin on the financial performance of Angkringan Gopel during 2016- 2020.